2014
DOI: 10.2337/db14-1020
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infection of Engrafted Human Islets Leads to Diabetes

Abstract: Type 1 diabetes (T1D) is characterized by the destruction of the insulin-producing β-cells of pancreatic islets. Genetic and environmental factors both contribute to T1D development. Viral infection with enteroviruses is a suspected trigger for T1D, but a causal role remains unproven and controversial. Studies in animals are problematic because of species-specific differences in host cell susceptibility and immune responses to candidate viral pathogens such as coxsackievirus B (CVB). In order to resolve the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 53 publications
(52 reference statements)
5
55
0
Order By: Relevance
“…Viral infection and innate immune activation may initiate early events in β-cells and/or immune cells that ultimately lead to autoimmune attack and T1D in genetically susceptible individuals. In the long term, findings from these studies could be transitioned to diabetes models involving human islets and human immune cells (56) in which type I IFN pathways are disrupted. The current data reinforce the need for novel approaches to diabetes prevention and treatment, such as viral vaccine development (57,58) or even cytokine-modulating therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Viral infection and innate immune activation may initiate early events in β-cells and/or immune cells that ultimately lead to autoimmune attack and T1D in genetically susceptible individuals. In the long term, findings from these studies could be transitioned to diabetes models involving human islets and human immune cells (56) in which type I IFN pathways are disrupted. The current data reinforce the need for novel approaches to diabetes prevention and treatment, such as viral vaccine development (57,58) or even cytokine-modulating therapies.…”
Section: Discussionmentioning
confidence: 99%
“…To begin to investigate possible mechanisms by which Coxsackie infection could trigger T1D, human islets were infected in vitro with Coxsackie virus, and it was demonstrated that the virus could directly infect human β cells, a mechanism of how the virus could detrimentally affect human β cells not previously recognized (132). When NSG mice were transplanted with human islets and infected with Coxsackie virus, almost half of the mice reverted to a hyperglycemic state and a human-specific gene expression of profiles in grafts from infected mice showed the induction of interferon signature genes, suggesting that the infected human islets may have a contributing role in their ultimate destruction by an autoimmune response (132). …”
Section: Humanized Mouse Models Of Autoimmunitymentioning
confidence: 99%
“…Along with their epidemiological associations (29,30), enterovirus infections of β cells impair insulin secretion (118), alter mRNA/miRNA expression (119,120), and induce interferon responses (121,122) that promote β cell stress, dysfunction, and apoptosis (123). Enteroviruses may also trigger autoimmunity via presentation of self-molecules in an inflammatory context (bystander activation) (124) and/or by molecular mimicry (125)(126)(127).…”
Section: Modified T Cell Autoantigens (Neoepitopes)mentioning
confidence: 99%